Delegation of the I.R.H. submitting a petition to the German consul-general asking for examination of the concentration camps in Germany. Persons named from left to right. From: Roode Hulp, 1933, September
Delegation of the I.R.H. submitting a petition to the German consul-general asking for examination of the concentration camps in Germany. Persons named from left to right. From: Roode Hulp, 1933, September.